Tecnologie di progetto per il terminal aeroportuale (2010)
Tecnologie di progetto per il terminal aeroportuale is the first scientific and educational textbook that applies research results to the sector of airport design. It brings together validated specialist methods to achieve the objectives of airport projects. The innovative aspect of this work relates to the fact that it clearly expounds the arguments, facilitating an understanding of the complex design issues facing this specific ambit. The results of research conducted with the support of funds from Florence University have been transformed into an updated handbook on the new design concepts and methods for the development of passenger terminals. The methods, the sector standards and the most scientifically advanced development tools are systematically presented through simple language and effective communication. The book is completed by technical factsheets for the design of the spatial units of the passenger terminals and by a review of recent international creations. These features of the publication make it suitable both for architects in the airport sector and as an aid to those professionals who wish to transfer the efficient methods illustrated to other design ambits.